NEEDS ANALYSIS FOR DESIGNING COMMUNICATIVE COMPETENCE-BASED SYLLABUS OF SPEAKING COURSE ONE IN THE DEPARTMENT OF ENGLISH EDUCATION AT STAIN PAREPARE - SELLE, AMZAH (P3M STAIN Parepare, 2014)
The problem is what are the studentsâ needs and the other stakeholdersâ expectations of the speaking course syllabus implemented in Department of English education at STAIN Parepare? The writer conducted needs analysis procedures to identify the linguistic needs and the learning needs of the students of English education study program. The data of the needs were collected by giving questionnaires to the respondents of this study i.e. the students, the lecturers, as well as the graduates. In order to obtain in-depth information on the needs and to cross check the data gathered from the questionnaires, interview was also used. The two types of instruments provide the perceptions and expectations of the students, the lecturers, and the graduates about the needs that should be available in the design of speaking course one syllabus. The perceptions of the students, the lecturers, and the graduates on needs analysis include the general perception of providing speaking subject in the English education study program, the perception associated with the linguistic needs in speaking course one syllabus, the perception according to the learning needs in speaking course one syllabus, and the overview of the design of speaking course one syllabus.